PENGETAHUAN DAN MOTIVASI ORANGTUA DALAM MEMBERIKAN VAKSIN PENCEGAH PNEUMONIA (HIB, PCV DAN CAMPAK) PADA BALITA DI YOGYAKARTA - Ririn Andriani; Masta Hutasoit (MEDIA ILMU KESEHATAN, 2019)
Background: Pneumonia is a disease that is a problem of high morbidity and mortality in children under 5 years of age. The incidence of pneumonia in Indonesia increased by 2.0% in 2018, Yogyakarta area the incidence of pneumonia by 26.61% in 2017. Parents are an important target for their children's health. The importance of knowledge and motivation to reduce the incidence of pneumonia in children. Objective: Knowing the relationship of knowledge with parents' motivation in providing Hib, PCV and Measles vaccines to prevent under five pneumonia in PKU Muhammadiyah Hospital, Yogyakarta City. Method: This research uses descriptive quantitative design with cross sectional approach. Sampling was carried out with a purposive sampling technique of 60 respondents. Retrieval of data using knowledge and motivation questionnaires and analyzed using the Gamma test. Result: Knowledge with parental motivation in preventing toddler pneumonia in PKU Muhammadiyah Hospital Yogyakarta obtained a level of parental knowledge of 66.7% in the good category and parental motivation of 76.7% in the high category. Gamma test results obtained p-value of 0.010 with a correlation coefficient of 0.587. Conclusions: There is a significant correlation between knowledge and parents' motivation in giving Hib, PCV and Measles vaccines to prevent under five pneumonia in PKU Muhammadiyah Hospital in Yogyakarta City with moderate relationship closeness.